INNOVATION TRENDS IN RHEUMATOID ARTHRITIS THERAPY DEVELOPMENT: MOLECULAR APPROACHES, IMMUNOTHERAPY, AND DRUG DELIVERY SYSTEMS - Shalu Herawati, Riska; Nisrina Kamilia; Shilkiaturrahma, Shinta (International Journal Multidisciplinary (IJMI), 2025)
Objective: This study explores the latest advancements in rheumatoid arthritis (RA) therapy, focusing on molecular approaches, immunotherapy, and drug delivery systems to enhance therapeutic efficacy and personalization. Method: A systematic review of scientific literature and bioinformatics analysis was conducted to identify molecular subgroups of RA and assess the effectiveness of innovative drug delivery systems, including pH-sensitive hydrogels and transfersomal formulations. Comparative studies between rituximab and tocilizumab were also analyzed, particularly in anti-TNF refractory patients. Results: The findings reveal three molecular subgroups of RA based on transcriptomic profiles, enabling more personalized therapeutic strategies. Advanced drug delivery systems demonstrated a 45% improvement in bioavailability compared to conventional oral formulations. Tocilizumab showed higher efficacy than rituximab in patients with low B-cell expression. However, immunogenicity challenges, with anti-drug antibodies reducing therapeutic efficacy by 40-60%, remain significant. Additionally, non-pharmacological therapies, such as acupuncture, reduced systemic complications, including dementia, by 22%. Novelty: This study highlights the importance of personalized RA treatment based on molecular profiling and introduces innovative drug delivery systems, marking a pivotal shift toward more effective and individualized therapeutic strategies. Future research should focus on more precise biomarker identification and tailored therapeutic approaches for distinct molecular subgroups.